Early rehabilitation after atnerior cruciate ligamente reconstruction - literature review - Wawryków, Agata; Stecko, Monika; Korabiusz, Katarzyna; Fabian-Danielewska, Anna; Wilczyńska, Agnieszka; Janik-Fuks, Inga; Maciejewska, Martyna (Journal of Education, Health and Sport, 2019)
Rehabilitation of patients after reconstruction of the anterior cruciate ligament is the subject of many physiotherapeutic discussions. Of all sports injuries, about 70% are damage to the knee joint. Among these, in turn, the injuries of the anterior cruciate ligament occupy the leading position. Reconstruction is the best way to recreate a damaged ACL. The return of the patient to full physical fitness and daily activities are conditioned by surgery and improvement procedures. Early rehabilitation, the selection of appropriate rehabilitation methods, as well as individual characteristics of the patient affect the acceleration of the rehabilitation procedure and the results achieved at particular stages of physiotherapy